Comparative politics a theoretical framework - Almond, Gabriel A. (Gabriel Abraham) 1911-2002 (HarperCollins College Publishers, 1995)
This text was created in response to demands for a brief version of the leading comparative politics text, Almond and Powell's Comparative Politics Today. The material focuses on the world-wide process of democratisation.